E-waste Generation, Awareness and Management in Third World Countries: Prospects and Challenges - Odili, Julius Beneoluchi; Noraziah, Adzhar; Ambar, Radzi; Abd. Wahab, Mohd Helmy; M. A. I., Fakheraldin (ISRES Publishing, 2018)
The millions of tonnes of e-wastes being annually as a result of development od science and technology since the 20this, to say the least, a time-bomb waiting for explosion with disastrous consequences, if left unchecked. This paper presents the outcome of a survey in e-waste generation, awareness and management in third world. Countries like Malaysia and Nigeria. The choice of these two countries (one from Africa and the other from Asia) is borne out of their strategic locations and activities in e-wastes generation cum management scale of preference. The paper examines the major present awareness level of e-wastes, individual, corporate and governmental contributions to e-wastes management and control, Using the Anchor University Lagos, Nigeria and the Universiti Malaysia Pahang, Kuantan, Malaysia as its locale, the paper investigates the awareness of e-wastes, hazards posed and efforts required to properly control and manage e-wastes in third world countries